The Changing military balance in the Koreas and Northeast Asia - Cordesman, Anthony H.; Lin, Aaron (Rowman & Littlefield, 2015)
This new volume, up to date through Spring 2015, provides a detailed examination of the military forces in Northeast Asia-North and South Korea, China, Russia, Japan, and the United States-setting those forces in the larger geostrategic context.